Mrs Pounds and Mrs Pfoundes - Bocking, Brian (Journal of the British Association for the Study of Religions, 2017)
In this short essay written for Professor Ursula King's Festschrift I reflect on the general problem of researching and recovering events and individuals previously lost' to historians of religions, taking as my example recent collaborative research into forgotten early Irish Buddhists. I consider also the problems of researching other traditionally under-represented figures, including many women; for example, the wife (Rosa Alice Hill) and mother (Caroline Pounds) of the Irish Buddhist Charles Pfoundes. In the second and rather more speculative part of the essay I look at some ways in which increasingly sophisticated and increasingly accessible technological developments, allied with growing crowd' participation in the provision and analysis of historical data, might in future enable us to discover far more than we currently can about events and individuals in the past.